THE EFFECT OF STEM PROJECT-BASED LEARNING ON STUDENTS' CREATIVITY AND MOTIVATION IN LEARNING HEAT TRANSFER - Ulvi Asdi Salikha, - (2020)
Indonesian education system changed several times to adapt to international developments leading to 21st century challenges. In order to respond the 21st century requirements, new models of learning were needed to improve the quality of education. One alternative learning strategy that can be used is the use of STEM project-based learning. The purpose of this study was to investigate the effect of STEM project-based learning on student creativity and motivation in learning heat transfer. The method used in this study was pre-experimental research using one group pretest-posttest design. The method used to collect samples is convenience sampling method. The participants were 26 7th grade junior high school students in Cikancung, Bandung. Based on the five stages of STEM project-based learning implementation, the results show that almost all stages of STEM project-based learning can be completed, except for the correction stage, which cannot be completed due to time limitations. Moreover, students' creativity in this research was assessed from their creative products with the Creative Product Analysis Matrix (CPAM), the result of the student creativity product indicates that the student's level of creativity is at a good level with a percentage of approximately 76.98 %. Furthermore, the use of STEM project-based learning also improves student motivation in learning science. Even though the value of N-gain <g> is 0.06, which is considered as low improvement, the statistical test by means of the paired sample t-test shows that there is a significant difference between the motivation of students before and after the STEM project-based learning. Based on these results, it has been shown that STEM project-based learning has a positive effect on student creativity and also improves student motivation. Moreover, STEM project-based learning could also be seen as an innovative model of learning that can be applied to junior high schools.